2015
DOI: 10.1016/j.jeurceramsoc.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical properties of low SWNT content 3YTZP composites

Abstract: Fully dense 3 mol% Y 2 O 3 -ZrO 2 (3YTZP) composites with low single wall carbon nanotube content (0.5, 1 and 1.5 vol% SWNT) were prepared by colloidal processing and Spark Plasma Sintering. SWNT were distributed at ceramic grain boundaries and also into agglomerates. Characterization of SWNT agglomerates indicated that increase in SWNT vol% does not imply an increase in agglomeration. SWNT agglomerate density was related to the evolution of hardness and fracture toughness with SWNT vol%. Electrical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 47 publications
3
26
0
1
Order By: Relevance
“…Interfacial bonding between 3YTZP ceramic grains and SWNT is not very strong [7], so when SWNTs are mostly located in GBs and more homogeneously distributed, more interconnected, their influence is larger, resulting in a reduced hardness value. Therefore, improving SWNT dispersion decreases hardness because it increases SWNT content in GBs, in an analogous way to the decrease in hardness reported as a consequence of increasing nominal SWNT content in 3YTZP/SWNT composites [7,43]. A larger area of GBs covered by SWNT also facilitates grain boundary sliding at high temperatures, which has been proved by creep tests [36].…”
Section: Mechanical Propertiesmentioning
confidence: 57%
See 4 more Smart Citations
“…Interfacial bonding between 3YTZP ceramic grains and SWNT is not very strong [7], so when SWNTs are mostly located in GBs and more homogeneously distributed, more interconnected, their influence is larger, resulting in a reduced hardness value. Therefore, improving SWNT dispersion decreases hardness because it increases SWNT content in GBs, in an analogous way to the decrease in hardness reported as a consequence of increasing nominal SWNT content in 3YTZP/SWNT composites [7,43]. A larger area of GBs covered by SWNT also facilitates grain boundary sliding at high temperatures, which has been proved by creep tests [36].…”
Section: Mechanical Propertiesmentioning
confidence: 57%
“…Raman spectra of the SWNT used in this study showed a not negligible D band (I D /I G~0 .30) which obviously increases I D /I G ratio of the corresponding composites. Smaller I D /I G ratios were obtained from composites prepared with similar methods but different SWNTs in previous works [7,43]. Raman spectra from composites C2, C4 and C5, prepared using high energy ultrasonic probe to improve dispersion present systematically a smaller I D /I G ratio than composites C1 and C3 processed with lower energy ultrasonic agitation (see values in Table 3), which indicates that the energy and working time of the ultrasonic probe was reasonable and did not damage the SWNT crystallographic integrity.…”
Section: Microstructurementioning
confidence: 75%
See 3 more Smart Citations